Avaliação dos efeitos do limite de gastos com pessoal sobre a contratação de serviços de terceiros nos municípios brasileiros - Maia, Francisco Fausto Augusto da Silva (2018)
The Fiscal Responsibility Law established a limit of personnel expenses in 60% of the Net Current Revenue in the municipalities, which, if not respected, gives rise to various restrictions and responsibilities, including the impossibility of hiring servants through a tender and obtaining financing. In this context, the objective of this study was to verify how the degree of commitment of personnel expenses affects expenses with outsourcing of services (individuals or legal entities) not considered in personnel expenses, in order to test the possibility of these items being used way to circumvent the legal limit imposed in art. 19 of the LRF. For this purpose, the discontinuous regression method was used around the limit of personnel expenses, based on the finances (expenses with third-party services classified in codes 3.3.90.39 and 3.3.90.36) of Brazilian municipalities in 2016. The results obtained do not support the hypothesis, and complementary estimates point to a reduction of per capita expenditure with third-party services when municipalities are in the imminence of hurting the limit imposed by the legislation.